Evolution of Flow-Diverter Endothelialization and Thrombus Organization in Giant Fusiform Aneurysms after Flow Diversion: A Histopathologic Study - Szikora, I. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Treatment of giant fusiform aneurysms with flow diverters has been associated with a relatively high rate of complications. Our goal was to study the evolution of flow-diverter endothelialization and thrombus organization at different time points after flow-diverter treatment in giant fusiform aneurysms to better understand reasons for flow-diverter thrombosis and delayed aneurysm ruptures. MATERIALS AND METHODS: Two giant anterior and 2 posterior circulation aneurysms, all of which had partially thrombosed before treatment, were studied. An unruptured, untreated posterior circulation aneurysm was used as a control. Each specimen was removed at 7 days or at 6, 9, or 13 months after flow-diverter treatment. The 3 patients who survived longer than 7 days were followed up by angiography and MR imaging. Formaldehyde-fixed paraffin-embedded sections were stained by using H&E, Van Gieson elastic, CD34, h-Caldesmon, and Picrosirius stains and studied by light microscopy. RESULTS: According to angiography, aneurysms were found to be obliterated partially at 6 and 9 months and completely at 13 months. MR imaging revealed that mass effect remained unchanged in each case. Sections of the flow diverter within the normal parent artery were covered by an endothelialized fibrous layer as early as 6 months, but there was no tissue coverage or endothelialization seen even at 13 months inside the aneurysm itself. Each treated aneurysm had a thin wall with complete lack of smooth muscle cells. No signs of thrombus organization were found at any of the time points studied. CONCLUSIONS: Endothelialization of the flow diverter in giant fusiform aneurysms may not occur and thrombus organization may not be initiated inside these aneurysms for as long as 1 year, which explains delayed flow-diverter thrombosis and the possibility of delayed ruptures.